2014
DOI: 10.5194/amt-7-1701-2014
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of atmospheric mixing layer height from radiosonde data

Abstract: Abstract. Mixing layer height (h) is an important parameter for understanding the transport process in the troposphere, air pollution, weather and climate change. Many methods have been proposed to determine h by identifying the turning point of the radiosonde profile. However, substantial differences have been observed in the existing methods (e.g. the potential temperature (θ ), relative humidity (RH), specific humidity (q) and atmospheric refractivity (N) methods). These differences are associated with the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(68 citation statements)
references
References 39 publications
2
57
0
3
Order By: Relevance
“…Table 1 provides the basic information of these calculation methods from the sounding profile data. For all these methods, we restricted the available data of all the sounding records to 4000 m to avoid mistaking free tropospheric features for the top of the boundary layer [18,47]. Moreover, to avoid spurious estimates of large vertical gradients resulting from horizontal (or vertical) separation of the surface instrument shelter from the radiosonde launch site, the height of the first level in the sounding was taken as the surface level [20].…”
Section: The Methods Used To Estimate the Blhmentioning
confidence: 99%
“…Table 1 provides the basic information of these calculation methods from the sounding profile data. For all these methods, we restricted the available data of all the sounding records to 4000 m to avoid mistaking free tropospheric features for the top of the boundary layer [18,47]. Moreover, to avoid spurious estimates of large vertical gradients resulting from horizontal (or vertical) separation of the surface instrument shelter from the radiosonde launch site, the height of the first level in the sounding was taken as the surface level [20].…”
Section: The Methods Used To Estimate the Blhmentioning
confidence: 99%
“…They are available twice daily from hundreds of sites globally, and there are several 2 Advances in Meteorology decades' worth of data available at many of these sites. For these reasons, rawinsonde observations are well-suited for climatological studies of PBL depth variability on seasonal to interannual timescales [20][21][22], despite known limitations in rawinsonde-derived PBL depth estimates [1,23].…”
Section: Introductionmentioning
confidence: 99%
“…Wang and Wang [7] considers mixing layer height (h) to be an important parameter that affects the near-surface air pollution concentration because it determines the volume in which the emitted pollutants are dispersed. The researcher also reported that h is related to the warming rate that is caused by the enhanced greenhouse gases.…”
Section: Ventilation and Build-up Of Pollutantsmentioning
confidence: 99%